2001
DOI: 10.1093/glycob/11.4.261
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Asn-linked glycans from vegetable foodstuffs: widespread occurrence of Lewis a, core  1,3-linked fucose and xylose substitutions

Abstract: The N-glycans from 27 "plant" foodstuffs, including one from a gymnospermic plant and one from a fungus, were prepared by a new procedure and examined by means of matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS). For several samples, glycan structures were additionally investigated by size-fractionation and reverse-phase high-performance liquid chromatography in conjunction with exoglycosidase digests and finally also (1)H-nuclear magnetic resonance spectroscopy. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
233
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(244 citation statements)
references
References 64 publications
7
233
1
Order By: Relevance
“…In this study, the deduced rS2C4-IgG1level is about 24 mg per liter (data not shown), with a good balance of heavy/light chains expression ( Figure 1C). The insect cell has a different post translational glycoprotein pattern from mammalian hosts (Wilson et al, 2001). However, many studies have reported that these differences do not affect IgG activities (Boyd et al, 1995), consistent with our results that rS2C4-IgG1 exerted in vitro and in vivo functions similar to its parent antibody.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the deduced rS2C4-IgG1level is about 24 mg per liter (data not shown), with a good balance of heavy/light chains expression ( Figure 1C). The insect cell has a different post translational glycoprotein pattern from mammalian hosts (Wilson et al, 2001). However, many studies have reported that these differences do not affect IgG activities (Boyd et al, 1995), consistent with our results that rS2C4-IgG1 exerted in vitro and in vivo functions similar to its parent antibody.…”
Section: Discussionsupporting
confidence: 90%
“…Lectin blotting (SI Materials and Methods) was performed using wheat germ agglutinin (binds to GlcNAc; Sigma) or G. nivalis agglutinin (binds to mannose; Roche). Glycoprotein-linked N-glycans and free N-glycans were isolated as described previously (37,38), with few modifications (SI Materials and Methods).…”
Section: Methodsmentioning
confidence: 99%
“…Second, peanut glycoproteins contain almost no fucose [14]. Anti-Xyl IgE never found above baseline -even in peanut allergic patients [Eiwegger T, Altmann F, Vienna, Austria; unpublished results].…”
Section: Biological Signi Cance Of Plant/insect Ccdsmentioning
confidence: 99%